A review of recent advances in bio-based polymer composite filaments for 3D printing. Issue 9 (13th June 2023) - Cakir Yigit, Nese; Karagoz, Idris
ABSTRACT: 3D printers are frequently preferred in producing parts as an alternative to traditional production by different sectors. The material extrusion method further comes to the forefront since the output is simple, can be used easily even by nonprofessionals, and has become widespread rapidly. However, one of the biggest challenges in the material extrusion method is limited raw materials used in production due to environmental sensitivity, cost, process difficulty, and the inappropriateness of the current materials for 3D printers. This limitation is one of the most significant obstacles to the further spread of the material extrusion method and the economical production of parts using it. Researchers have recommended using many polymer composites and nanocomposites as filaments. However, despite their excellent mechanical properties, most new petroleum-based polymer materials are not biodegradable. This study examines the current progress on innovative green composite filaments, which are natural, economical, recyclable, biodegradable, and sustainable and can be an alternative to petroleum-based plastics, as a solution to this problem and presents the latest situation to researchers. With the development of new types of biodegradable materials to be used in the material extrusion method, the production perspective and methods will radically change in many sectors in the future.